The impact of altered polyprotein ratios on the assembly and infectivity of Mason-Pfizer monkey virus - Kohoutová, Zdena; Rumlová, Michaela; Andreánsky, Martin; Sakalian, Michael; Hunter, Eric; Pichová, Iva; Ruml, Tomás (Virology, 2009)
Most retroviruses employ a frameshift mechanism during polyprotein synthesis to balance appropriate ratios of structural proteins and enzymes. To investigate the requirements for individual precursors in retrovirus assembly, we modified the polyprotein repertoire of Mason-Pfizer monkey virus (M-PMV) by mutating the frameshift sites to imitate the polyprotein organization of Rous sarcoma virus (Gag-Pro and Gag-Pro-Pol) or Human immunodeficiency virus (Gag and Gag-Pro-Pol). For the "Rous-like" virus, assembly was impaired with no incorporation of Gag-Pro-Pol into particles and for the "HIV-like" virus an altered morphogenesis was observed. A mutant expressing Gag and Gag-Pro polyproteins and lacking Gag-Pro-Pol assembled intracellular particles at a level similar to the wild-type. Gag-Pro-Pol polyprotein alone neither formed immature particles nor processed the precursor. All the mutants were non-infectious except the "HIV-like", which retained fractional infectivity.
Keywords: Masonův-Pfizerův opičí virus; Chlorocebus aethiops; RNA virová; Humans; AIDS opičí; messenger RNA; Simian Acquired Immunodeficiency Syndrome; Frameshift Mutation; Viral Proteins; Rous sarcoma virus; COS Cells; virion; Gene Products, pol; genové produkty gag; Mason-Pfizer monkey virus; lidé; zvířata; posunová mutace; Cercopithecus aethiops; transfekce; RNA, Messenger; COS buňky; proteosyntéza; virové proteiny; Virion; virus Rousova sarkomu; RNA, Viral; Transfection; Animals; genové produkty pol; Protein Biosynthesis; Gene Products, gag